A Cautionary Tale of Environmental Management: Malaria, Water Management, and Land Reclamation in Twentieth-Century Guatemala. Issue 3 (17th May 2021) - Carey, David
Abstract: In the late 1920s, Guatemala embarked on environmental drainage projects aimed at eradicating mosquito breeding grounds. Designed to improve people's lives, these efforts sometimes inadvertently undermined them, draining away water crucial to public hygiene campaigns. Although the goals of controlling malaria and expanding arable land were often in lockstep, the Guatemalan case of Lake Quinizilapa requires a more nuanced analysis. Bringing the historiographies of the environment and public health and medicine to bear on environmental management projects, this article demonstrates that environmental management and scientific medicine were as much about leveraging disease as eradicating it. Whereas Hispanic authorities could maintain theories disproven by entomology and parasitology without much criticism, indígenas (indigenous people) who articulated notions that contradicted science and challenged engineering's supremacy were disparaged as ignorant inditos (little Indians). Intriguingly, the indigenous conception of the natural world more accurately predicted the outcome of the lake's drainage prior to World War II. Political power and ethnicity determined the legitimacy of perspectives about the environment and disease.